2021
DOI: 10.1007/s13202-021-01160-y
|View full text |Cite
|
Sign up to set email alerts
|

Rock analysis to characterize Saudi soft sandstone rock

Abstract: As more engineering projects and activities are taking place on and around weak rocks, it is becoming more important to study and characterize them. Since regular practices of rock mechanical testing are not effective for weak rocks, special laboratory tests and measurements were performed to characterize the Alkharj Saudi weak sandstone rock which is a clastic rock dominantly sandy limestone and sandstone. Test results are presented in this paper. Porosity, permeability, and mechanical properties (stress, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Te results of laboratory tests show that the failure strain of mudstone is 0.018-0.02, and of the coal is 0.012-0.016 (Figure 3). Tis corresponds with the results of testing soft rock specimens in a volumetric feld [36][37][38] and under uniaxial compression [39,40]. According to the results of tests, it was found that for mudstone, siltstone, argillite, and sandstone with uniaxial strength of 25-40 MPa, the failure criteria for strain is about 0.02-0.03.…”
Section: Simulation Resultssupporting
confidence: 72%
“…Te results of laboratory tests show that the failure strain of mudstone is 0.018-0.02, and of the coal is 0.012-0.016 (Figure 3). Tis corresponds with the results of testing soft rock specimens in a volumetric feld [36][37][38] and under uniaxial compression [39,40]. According to the results of tests, it was found that for mudstone, siltstone, argillite, and sandstone with uniaxial strength of 25-40 MPa, the failure criteria for strain is about 0.02-0.03.…”
Section: Simulation Resultssupporting
confidence: 72%
“…The results of rock specimen tests show [52][53][54][55] that for mudstone, siltstone, argillite, and sandstone with a uniaxial strength of 25-40 MPa, the failure criterion for strain is about 0.02-0.03. Therefore, in the numerical simulation, the post-peak limit was accepted in the range of "−0.02"-"+0.02".…”
Section: Simulation Resultsmentioning
confidence: 99%
“…According to the results of testing soft rocks specimen in a volumetric field [34][35][36] and under uniaxial compression [37][38][39][40][41], it was found that for mudstone, siltstone, argillite, shale, and sandstone with a strength of 25-40 MPa, the failure criteria for strain is about 0.03. The surfaces of elastic and plastic strains are shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%